PENGARUH PEMBERIAN PUPUK KOTORAN SAPI DAN VOLUME AIR YANG BERBEDA DENGAN SISTEM IRIGASI TETES TERHADAP PERTUMBUHAN TANAMAN MELON (Cucumis melo L.) DI LAHAN TAILING - Sitti Nurul Aini; Ratna Santi; Deni Pratama; Eva Helda; Ratmo Miwandes Sinaga (Universitas Trilogi, 2020)
Post tin mining tailings land in Bangka Belitung Islands Province has an area of around 400 000 ha. In terms of area, the land has the potential to be used as cultivated land, one of which is melon. The aims of the study is to see the effect of cow manure fertilizer and drip irrigation water volume on melon plants growth in post tin mining tailings area. This research was conducted from June to August 2018 in the tailings area of Dewi Makmur Village, Merawang District, Bangka Regency. This experimental used a completely randomized design (CRD) factorial method. The first factor was cow manure with three levels (K1 = 2.5 kg/planting hole; K2 = 5 kg / planting hole; K3 = 7.5 kg / planting hole) and the second factor was drip irrigation volume (A1 = 800 ml; A2 = 1 500 ml). The results showed that giving cow manure and water irrigatian has no significant effect on melon plant height, stem diameter and number of leaves, but the treatment 7.5 kg of cow manure and 1 500 ml water gave results that tended to be better.